Uso de diferentes inóculos na digestão anaeróbia da cama de aviário - Bortolini, Joseane (2016)
The increasing population development has contributed to a significant increase in consumption and consequently poultry production, which results in a larger waste generation, since poultry litter receives excreta. One of the alternatives to treat waste and find a final disposal to it in this trial is the anaerobic digestion of poultry litter (PL), which not only generates bio-fertilizer, but also produces biogas. However, digester starting as well as quality and quantity of generated biogas are associated to the material to be digested and with the same operating conditions, since they are factors for inocula application. Thus, this study aimed to investigate the influence of digestate application as inoculum at anaerobic digestion from poultry litter. Firstly, specific biomethanogenic potential tests were carried out from poultry litter and there was a test to check if the digestate use as inocula has influenced on biogas production. Finally, this trial was carried out and inocula were tested (beef and swine digestate) during anaerobic digestion process of poultry litter, with daily diet, according to the volumetric loads that were tested - 0.67; 1.00; and 1.67 gSV.L-1day-1. It was concluded that poultry litter can be used as substrate in anaerobic digestion process and that digestate application as inoculum has shown adequate results regarding biogas production, since the treatment without inoculum addition showed the lowest biogas answers. So, when the inocula were compared with one another (beef and swine digestate), it was concluded that both of them are indicated in the digestion process with poultry litter. However, bovine inoculum showed the highest values of biogas and methane production, and also the lowest values in relation to the percentages of neutral detergent fiber (NDF), acid detergent fiber (ADF) and lignin (LIG), highlighting the advantages of its use as inoculum due to its greater capacity to degrade fibrous fractions.